Epidemiological investigation and pathogenicity of porcine reproductive and respiratory syndrome virus in Sichuan, China - Jiang, Dike; Tu, Teng; Zhou, You; Li, Yanwei; Luo, Yan; Yao, Xueping; Yang, Zexiao; Ren, Meishen; Wang, Yin (Frontiers in Microbiology, 2023)
Porcine reproductive and respiratory syndrome virus type 2 (PRRSV-2) lineage 8 was first detected in mainland China in 2006 and has since rapidly spread to become the primary epidemic strain in the country. In this study, samples such as lung tissue, hilar lymph nodes, abortion fetuses, and blood were collected from large-scale pig farms across 11 prefecture-level cities in Sichuan province between 2019 and 2020 for antigen detection and PRRS virus isolation. The antigen detection results indicated that the positive rate of HP-PRRSV (JXA1-Like strain) was 44.74% (51/114), NADC30-Like PRRSV was 17.54% (20/114), and classical PRRSV (VR2332-Like strain) was 37.72% (43/114). The predominant strain was HP-PRRSV. Positive samples were further inoculated into Marc-145 cells for virus isolation and identification, leading to the isolation of a new JXA1-Like PRRSV strain named SCSN2020. The strain was characterized by RT-qPCR, indirect immunofluorescence assay (IFA), plaque purification, electron microscopy, and whole genome sequencing. The total length of the viral genome was determined to be approximately 15,374 bp. A comparison of the SCSN2020 genome with VR2332 revealed that both strains had the same discontinuous 30-amino acid deletion on the Nsp2 gene. ORF5 genotyping classified the SCSN2020 strain as sublineage 8.7, with a whole genome sequence identity of 99.34% with JXA1. Furthermore, we evaluated the pathogenicity of the SCSN2020 strain in 28-day-old piglets and observed persistent fever from day 4 to day 10, weight loss started on day 7, dyspnea and severe lung lesions began started on day 14. The results of this study highlight the current PRRSV epidemic situation in Sichuan province and provide a scientific reference for subsequent prevention and control measures.